Cytotoxic prenylated xanthone and coumarin derivatives from Malaysian Mesua beccariana. (September 2016) - Karunakaran, Thiruventhan; Ee, Gwendoline C.L.; Tee, Keng H.; Ismail, Intan S.; Zamakshshari, Nor H.; Peter, Waziri M.
Graphical abstract: Highlights: ⿢ The stem bark of Mesua beccariana gave beccarixanthone T and beccamarin T. ⿢ Beccarixanthone T and beccamarin T are new natural products. ⿢ Beccarixanthone T and beccamarin T gave some cytotoxic activities against Hep G2 and HT-29 cell lines. Abstract: Our recent research on the phytochemical constituents of the stem bark of Mesua beccariana gave one new xanthone, beccarixanthone T (1 ) and one new coumarin, beccamarin T (2 ) together with three known xanthones mesuarianone (3 ), mesuasinone (4 ), 1, 5-dihydroxyxanthone (5 ) and four known terpenoids, friedelin (6 ), stigmasterol (7 ), beta-sitosterol (8 ) and gamma-sitosterol (9 ). The structures of these compounds were elucidated and determined using spectroscopic techniques such as NMR and MS. The cytotoxic activities of compounds1-4 as well as the crude extracts were tested against two cancer cell lines, Hep G2 (liver cancer cell line) and HT-29 (colon cancer cell line) using MTT assays. Mesuarianone (3 ) gave a significant activity on the HT-29 cell line while mesuasinone (4 ) gave moderate activity against HT-29 cell line.